A Conformação da tutela provisória de urgência inaudita altera pars ao formalismo-valorativo no código de processo civil de 2015 - TRINDADE, Welber Rodrigues (2022)
This Course Conclusion Paper aims to address the foundations of evaluative formalism as a theory of civil procedural law and analyze the conformation of the inaudita altera pars provisional tutelage of urgency, in the Brazilian Civil Procedure Code of 2015, to the foundations of that theory which is considered as the current methodological phase of the Brazilian procedural system. The evaluative formalism is based on the view of civil procedural law from a constitutional perspective, formed by dialogue and argumentation, and presents as the most important principles the cooperation of procedural agents, the effective contradictory and the motivation of judicial decisions. The inaudita altera pars provisional tutelage of urgency is founded on summary cognition and is granted without the prior participation of the defendant. The research, carried out by the bibliographic method, seeks to analyze whether this institute is in accordance with the bases of the addressed procedural theory, especially in relation to the principles of contradictory and motivation, and concludes by the conformity of this institute with evaluative formalism.